EFFECTS OF DIAGENESIS ON THE ISOTOPIC RECORD OF LATE PALEOGENE TROPICAL SEA SURFACE TEMPERATURES - Schrag D.P. (My University, 1999)
Oxygen isotope records of planktonic foraminifera indicate that Late Eocene and Oligocene tropical sea surface temperatures were as much as 8°C lower than present at a time when high latitude sea surface temperatures were higher than present. Using a numerical model which describes oxygen isotope exchange during burial and recrystallization of deep sea carbonate, the effects of diagenesis on bulk carbonate δ18O records for the Cenozoic are quantified for four tropical sites. Most of the observed variations in measured δ18O values at all sites can be accounted for by diagenetic effects. There are no systematic trends that support substantial variations in tropical sea surface temperatures beyond diagenetic effects, with the possible exception of the Early Eocene for which the data are consistent with slightly higher sea surface temperatures. Reconstructions based on oxygen isotope records of planktonic foraminifera which indicate cooler tropical sea surface temperatures for the Eocene and Oligocene may be artifacts of diagenetic recrystallization as such records are particularly sensitive to diagenetic effects.
Keywords: DIAGENESIS; CENOZOIC; LATE PALEOGENE; Cenozoic; Cenozoic::Paleogene; Кайнозой; Кайнозой::Палеоген